Inter-relação entre o balanço cátion-aniônico do alimento e o ph urinário de gatos - Pires, Carolina Padovani; de Oliveira Borges Saad, Flávia Maria; Carciofi, Aulus Cavalieri [UNESP]; Santos, João Paulo Fernandes (My University, 2011)
Studies for the food development of formulations for pets, look for key components to maintaining healthy way of life and safety of products, including these, elements capable of preventing the risk of certain metabolic disorders associated with diet. Feline urinarytract disorders, highlights the urolithiasis, have high incidence in clinical series. Studies linking dietary factors such as ingredients, digestibility and chemical composition, changing the volume, density and pH of urine and consequent induction training for urolithiasis. A highly significant correlation between the mineral composition of the diet and urine pH of cats began to be studied, using the association between the cation-anion balance of the diet (DCAB) and regulation of acid-base balance of the body. The DCAB can be defined as the difference between the total fixed anions and cations present in the diet, important tool for estimating the urinary pH and to determine the range of pH that favors the food used, thereby linking the trigger and the prevention of struvite and calcium oxalate urolithiasis in the urinary tract of cats. Thus, this review aims to clarify the effects of the nutritional composition of diet on urine pH in cats.
Inter-relation between diet cation-anion balance and urinary ph in cats
Keywords: Base excess; Cats; Nutrition; Urine